Actual use of pocket-sized ultrasound devices for cardiovascular examination by trained physicians during a hospitalist rotation - Benjamin T. Tsai; Eric B. Dahms; Jill Waalen; Bruce J. Kimura (Greater Baltimore Medical Center, 2016)
Background: In actual clinical practice as opposed to published studies, the application of bedside ultrasound requires a perception of need, confidence in one's skills, and convenience. Objective: As the frequency of ultrasound usage is evidence to its perceived value in patient care, we observed the pattern of autonomous use of a pocket-sized device (PSD) by ultrasound-trained residents during a night hospitalist rotation. Methods: Consecutive internal medicine residents (n=24), trained in a cardiac limited ultrasound examination (CLUE) as a mandatory part of their curriculum, were sampled on their PSD use after their admitting nights, regarding perceived necessity, deterring factors, detected abnormalities, and imaging difficulties. A detailed analysis was performed with one resident who used a PSD on every admission to compare the proportion of abnormal CLUEs and utility in patients with and without a perceived need. Results: Residents admitted 542 patients (mean age: 55±17 years, range: 17-95 years) during 101 shifts and performed CLUE on 230 patients (42%, range: 17-85%). Residents elected not to scan 312 (58%) patients due to 1) lack of perceived necessity (231, 74%), 2) time constraints (44, 14%), and 3) patient barriers (37, 12%). In the detailed analysis (n=71), the resident felt CLUE was necessary in 32 (45%) patients versus unnecessary in 39 (55%) patients, with abnormality rates of 50% versus 20.5% (p=0.01) and utility rates of 28.1% versus 15.4% (p=0.25), respectively. Conclusion: When unbiased residents acting as hospitalists are provided with a PSD to augment initial cardiac examination, usage is frequent and suggests clinical value in hospital medicine.